A rapid and highly sensitive strain-effect graphene-based bio-sensor for the detection of stroke and cancer bio-markers. Issue 17 (6th April 2018) - Lin, Duo; Tseng, Chinh-Yu; Lim, Qi Feng; Tan, Mein Jin; Kong, Kien Voon
Abstract : A bio-sensor for the detection of cancer biomarkers utilizing the adsorption properties of ruthenium carbonyl on monolayer graphene. Abstract : Here, we propose a highly sensitive and rapid bio-sensor for the detection of bio-markers for stroke and cancer-related diseases, based on the utilization of the adsorption properties of ruthenium carbonyl (Ru–CO) clusters on monolayer graphene (MG). A fast rate of decarbonylation of Ru–CO to form ruthenium oxide nanoparticles (RuO2 NPs) on MG was observed. The quantitative detection of matrix metalloproteinase-2 (MMP-2) (bio-marker for stroke and vascular diseases) was demonstrated by tracking the spectral shift of the characteristic G band of graphene caused by the adsorption of RuO2 NPs. A concentration as low as 17 ng mL −1 of MMP-2 was detected in a simulated clinical serum sample. This effective bio-sensor has the potential to revolutionize the biomedical field in the early detection and possible prevention of stroke and cancer diagnosis.